2020
DOI: 10.3390/molecules25133087
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Metabolic Changes of the Crust from Dry-Aged Beef Using 2D NMR Spectroscopy

Abstract: Two-dimensional quantitative nuclear magnetic resonance (2D qNMR)-based metabolomics was performed to understand characteristic metabolic profiles in different aging regimes (crust from dry-aged beef, inner edible flesh of dry-aged beef, and wet-aged beef striploin) over 4 weeks. Samples were extracted using 0.6 M perchlorate to acquire polar metabolites. Partial least squares-discriminant analysis showed a good cumulative explained variation (R2 = 0.967) and predictive ability (Q2 = 0.935). Metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 50 publications
6
28
0
Order By: Relevance
“…Few ranked metabolites such as 2-aminoadipic acid and myo-inositol have rarely been reported in poultry meat. Additionally, metabolites undergo proteolytic enzyme cleavage and nucleotide degradation during the transition from muscle to meat and metabolic concentrations and end products can also change depending on the sex, species, and age ( Jayasena et al, 2014b ; Jung et al, 2013 ; Kim et al, 2020a ; Ryu and Kim, 2005 ), suggesting that further analysis may be necessary to identify critical metabolic properties in these animals. However, despite this, our data were in agreement with those reported in previous studies which suggested that the combination of qNMR and multivariate analysis could elucidate metabolic characteristics of samples in the absence of numerical quantification ( Kim et al., 2020a ; Kim et al, 2020b ; Winning et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Few ranked metabolites such as 2-aminoadipic acid and myo-inositol have rarely been reported in poultry meat. Additionally, metabolites undergo proteolytic enzyme cleavage and nucleotide degradation during the transition from muscle to meat and metabolic concentrations and end products can also change depending on the sex, species, and age ( Jayasena et al, 2014b ; Jung et al, 2013 ; Kim et al, 2020a ; Ryu and Kim, 2005 ), suggesting that further analysis may be necessary to identify critical metabolic properties in these animals. However, despite this, our data were in agreement with those reported in previous studies which suggested that the combination of qNMR and multivariate analysis could elucidate metabolic characteristics of samples in the absence of numerical quantification ( Kim et al., 2020a ; Kim et al, 2020b ; Winning et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Metabolites in the 1D 1 H NMR analysis were quantified using methods described by Kim et al (2019) . Prior to multivariate comparison, peak intensities in the 1 H- 13 C HSQC data were quantified using AMIX (Analysis of MIXtures software v3.9, Bruker Biospin GmbH) according to the methods described by Kim et al (2020a) .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations